(untitled) (Research, Society and Development, 2023)
Objective: to track the risk of sarcopenia and associated factors in hospitalized elderly, applying the SARC-F and SARC-CALF screening methods. Methodology: this is a cross-sectional study carried out between May and October 2022 in elderly people admitted to the emergency room of a public hospital. Information regarding age, gender, diagnosis and comorbidities was collected from medical records. Socioeconomic data were obtained through a questionnaire. Nutritional risk screening, anthropometric assessment and application of the SARC-F and SARC-CALF screening tools were performed. The association between risk of sarcopenia and independent variables was obtained through binary logistic regression, using odds ratio (OR) and 95% confidence interval. They were considered associated with variables that presented a significance level of 5%. Results: 225 elderly were evaluated, 53.3% were at risk of sarcopenia according to the SARC-F and 49.8% according to the SARC-CALF. Both tools were associated with the female gender, age greater than or equal to 80 years, risk of malnutrition and malnutrition according to the MAN. Only SARC-F was associated with previous diseases. Only the SARC-CALF associated schooling, nutritional status and adductor pollicis muscle thickness depletion. Conclusion: both tools proved to be viable, low-cost and easy-to-apply methods. It was observed that the number of elderly people admitted to the hospital at risk of sarcopenia is high. Thus, it is extremely important to include the application of sarcopenia screenings in the admission routine, to guide health professionals and provide intervention aimed at the prevention and recovery of these individuals.